The elements of building civilization and its challenges through surat an-NamL: An applied comparative study between Malaysia and Egypt / Ahmed Hassan Mohammed Ali Said - Ahmed Hassan , Mohammed Ali Said (2022)
This study deals with the elements of civilization building and its challenges, as found in Surat An-Naml, and compares between Malaysia and Egypt as a case study. The importance of this study is derived from its first reference: the Holy Qur’an, which caters for the peoples’ immediate and future interests. This study differs from previous studies, in theory, as it addresses the elements of civilization building and the challenges through Surat Al-Naml, and in practice, by applying the study to Malaysia and Egypt. The aim of the study has been to identify the concept of civilization in the Holy Qur’an, and in Western thought. The inductive method was followed, by tracing through and identifying the verses dealing with the elements of civilization building and challenges in Surat al-Naml. The study also relied on the descriptive analytical method, where the questionnaire was the chosen a tool for collecting primary data. The comparative method was used for comparing Islamic civilizational thought with the western civilizational thought, and for comparing the civilized situation on the ground between Malaysia and Egypt. A number of findings were reached. The elements of civilization and the challenges were amazingly detailed in Surat Al-Naml. The civilization aspects, as outlined in the Holy Qur’an, include both the material and the spiritual aspects, together, as inseparable pair, side by side. The most important differences in the concept of civilization between the Qur’anic and Western perspectives are that the Qur’anic perspective takes into account the interests of the real world and the afterlife, together, and that it weighs the benefits and evils with the scale of Islamic law. In contrast, the Western perspective is restricted to the worldly interests that humans themselves define with their limited knowledge. The field study showed that Malaysia had understood the elements of civilization building and managed to achieve scientific and practical development in the sectors of education, health, industry, transportation, and tourism, whereas Egypt had failed in these areas because of its reluctance to adopt civilization building true approach.